Parent-Reported Changes in Ontario Children's Physical Activity Levels during the COVID-19 Pandemic - Monika Szpunar; Matthew Bourke; Leigh M. Vanderloo; Brianne A. Bruijns; Stephanie Truelove; Shauna M. Burke; Jason Gilliland; Jennifer D. Irwin; Patricia Tucker (MDPI AG, 2023)
The COVID-19 pandemic resulted in closures of physical-activity-supporting environments, including playgrounds, outdoor recreation facilities (e.g., basketball courts), and community centers, which impacted children's movement opportunities. This study evaluated changes in Ontario children's physical activity levels during the COVID-19 pandemic and explored the impact of family sociodemographic markers on children's activity. Parents (n = 243; Mage = 38.8 years) of children aged 12 and under (n = 408; Mage = 6.7 years) living in Ontario, Canada, completed two online surveys between August and December 2020 (survey 1) and August and December 2021 (survey 2). Generalized linear mixed-effects models were used to estimate changes in the proportion of children who accumulated 60 min of physical activity per day pre-lockdown, during lockdown, and post-lockdown in Ontario. Results revealed a significant non-linear trajectory whereby the proportion of children achieving 60 min of physical activity per day pre-lockdown (63%) declined during lockdown (21%) and then increased post-lockdown (54%). Changes in the proportion of children engaging in 60 min of daily physical activity were moderated by several demographic variables. Efforts are needed to provide parents of young children with a wider variety of resources to ensure children are obtaining sufficient levels of physical activity regardless of the presence of community lockdowns.